2011
DOI: 10.1111/j.1746-1561.2010.00571.x
|View full text |Cite
|
Sign up to set email alerts
|

School Nurses' Perceived Barriers to Discussing Weight With Children and Their Families: A Qualitative Approach

Abstract: As expected, the use of focus group methodology yielded evidence of barriers to communication that had not been previously identified in the literature, as well as those that had been well documented. Consistent with a socioecological view of pediatric healthcare, results suggest a number of systems that could be targeted to improve nurses' weight-related communications with families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
129
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(141 citation statements)
references
References 26 publications
(89 reference statements)
10
129
2
Order By: Relevance
“…Over 70% of nurses in both studies found that one of the major factors is lack of parental concern. This was confirmed by DiNapoli, Sytnyk [20] and Steele, Wu [21] (see Table 2). Similarly, Nauta, Byrne, [17] Moyers, Bugle [18] and Steele, Wu [21] confirmed that unhealthy food available at school and non-nutritious foods contribute to childhood overweight/obesity.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Over 70% of nurses in both studies found that one of the major factors is lack of parental concern. This was confirmed by DiNapoli, Sytnyk [20] and Steele, Wu [21] (see Table 2). Similarly, Nauta, Byrne, [17] Moyers, Bugle [18] and Steele, Wu [21] confirmed that unhealthy food available at school and non-nutritious foods contribute to childhood overweight/obesity.…”
Section: Resultssupporting
confidence: 70%
“…52 [20] 9% of nurses perceive lack of parental motivation is the barrier to provide obesity education. Steele et al, [21] 1. Family characteristics (motivation, culture, resources, language, body size perceptions) 2.…”
Section: Resultsmentioning
confidence: 99%
“…HCPs themselves may also be poor at visually recognizing a child's overweight (Robinson, 2017; Smith, Gately, & Rudolf, 2008), so unless they employ objective tools the opportunity for weight‐related discussions may be missed. Whilst HCPs in this review were cognizant of the impact of societal perceptions of overweight on their interactions with parents, they seemed less concerned with the impact of their own weight and lifestyle (personal weight challenges were only cited in 1/13 studies (Steele et al ., 2011)). Health professionals may often be overweight themselves, not always eating a healthy diet or partaking in sufficient PA (Esposito & Fitzpatrick, 2011; Kaur & Walia, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…At this stage, these emergent themes and subthemes were identified by the research team as being broadly consistent with the levels of the socio‐ecological model (SEM) (Bronfenbrenner, 1992; Davison & Birch, 2001). The SEM has been previously applied to research in child weight (Davison & Birch, 2001; Huang & Glass, 2008; Steele et al ., 2011). By highlighting the importance of considering influences at the intrapersonal, interpersonal, and organizational/societal levels (Neuhauser & Kreps, 2003), the model helps to conceptualize the range of factors that contribute to this complex topic and identify potential areas for change within a particular organization/setting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation